2004
DOI: 10.1161/01.atv.0000124102.11472.36
|View full text |Cite
|
Sign up to set email alerts
|

CXCL16/SR-PSOX Is an Interferon-γ–Regulated Chemokine and Scavenger Receptor Expressed in Atherosclerotic Lesions

Abstract: Objective-Atherosclerosis is an inflammatory disease. Several chemokines are important for monocyte/macrophage and T-cell recruitment to the lesion. CXCL16 is a recently discovered chemokine that is expressed in soluble and transmembrane forms, ligates CXCR6 chemokine receptor, and guides migration of activated Th1 and Tc1 cells. It is identical to scavenger receptor SR-PSOX, which mediates uptake of oxidized low-density lipoprotein. We investigated whether CXCL16 expression is controlled by interferon-␥ (IFN-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
138
0
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 181 publications
(146 citation statements)
references
References 20 publications
4
138
0
4
Order By: Relevance
“…Both CXCR6 and its ligand CXCL16 have been implicated in the pathogenesis of atherosclerosis by virtue of their expression within the atherosclerotic lesions of humans and apolipoprotein Edeficient mice [8,24]. Recent data from studies using mice deficient in either CXCR6 or CXCL16 support a role for both ligand and receptor in atherogenesis [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Both CXCR6 and its ligand CXCL16 have been implicated in the pathogenesis of atherosclerosis by virtue of their expression within the atherosclerotic lesions of humans and apolipoprotein Edeficient mice [8,24]. Recent data from studies using mice deficient in either CXCR6 or CXCL16 support a role for both ligand and receptor in atherogenesis [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Firststrand complementary DNA (cDNA) was synthesized using oligo(dT) [12][13][14][15][16][17][18] primers (Amersham Pharmacia Biotech, Piscat-away, NJ) and SuperScript II reverse transcriptase (Invitrogen). The amount of cDNA for amplification was adjusted to the amount of RNA measured by optical density meter as well as ␤-actin polymerase chain reaction (PCR) products, using serially diluted cDNA.…”
Section: Methodsmentioning
confidence: 99%
“…We therefore determined the effect of the ERK1/2 inhibitor PD98059 on the IFN-g-induced uptake of AcLDL by THP-1 macrophages. THP-1 macrophages are used extensively to study macrophage foam cell formation, including the action of IFN-g, and express all the major proteins involved in this process, including scavenger receptors (8,(19)(20)(21). Initial experiments showed that maximal AcLDL uptake occurred at 24 h, which was therefore used for all subsequent experiments.…”
Section: Ifn-g Activates Erk In Macrophagesmentioning
confidence: 99%